2013
DOI: 10.1091/mbc.e12-12-0891
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor miR-375 regulates MYC expression via repression of CIP2A coding sequence through multiple miRNA–mRNA interactions

Abstract: miR-375 interacts with five conserved target sites in the CIP2A coding region, whereas the CIP2A 3′ UTR is not conserved across mammalian species. Reexpression of the tumor suppressor miR-375 in cancer cells represses the expression of CIP2A, resulting in a decrease in the MYC protein level and leading to reduced cell proliferation, migration, and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 70 publications
8
73
1
Order By: Relevance
“…Jung and his colleagues showed that four anti-cancer drugs (doxorubicin, 5-fluorouracil, trichostatin A and etoposide) could induce the expression of tumor suppressor miR-375 in tongue cancer [24]. This research group also testified that underexpression of tumor suppressor miR-375 contributes to promoting cancerous phenotypes by inducing uncontrolled CIP2A expression and extended stability of MYC [25]. Meanwhile, they showed that miR-375 activates p21 and suppresses telomerase activity by coordinately regulating HPV E6/E7, E6AP, CIP2A, and 14-3-3ζ [26].…”
Section: Discussionmentioning
confidence: 99%
“…Jung and his colleagues showed that four anti-cancer drugs (doxorubicin, 5-fluorouracil, trichostatin A and etoposide) could induce the expression of tumor suppressor miR-375 in tongue cancer [24]. This research group also testified that underexpression of tumor suppressor miR-375 contributes to promoting cancerous phenotypes by inducing uncontrolled CIP2A expression and extended stability of MYC [25]. Meanwhile, they showed that miR-375 activates p21 and suppresses telomerase activity by coordinately regulating HPV E6/E7, E6AP, CIP2A, and 14-3-3ζ [26].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance this result seems to vary from our observations. However, several studies have reported that miR-375 acts not as a positive regulator of cell proliferation but rather as a negative modulator (24,(34)(35)(36). At least two scenarios could account for this apparent divergence.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] CIP2A stabilizes MYC through its inhibitory effect on PPP2. Immunoblot for CIP2A in ctrl and LAMP2A (-) cells with or without transduction with wild-type MYC (Fig.…”
Section: Cma Control Of Myc Accumulation Is Dependent On Myc Phosphormentioning
confidence: 99%